A methodological approach to analysis and evaluation of decision systems - Lee, M.J.; Ernst, R.L. (COMPSAC 79. Proceedings. Computer Software and The IEEE Computer Society's Third International Applications Conference, 1979, 1979)
The purpose of this research was to develop a basis for a more coherent methodology for the design, implementation, and evaluation of decision systems. The methodology consists of applying Markovian and Bayesian probability techniques to the analysis of evaluated decision maker responses with respect to display information in sequential decision making. A configuration of display information was analyzed. Utilizing Monte Carlo techniques, a decision situation was simulated with human subjects serving as decision makers. Results of this study indicate that the performance of decision makers is directly associated with the quality of information presented.